2020
DOI: 10.1007/s13659-020-00272-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects and Mechanisms of Rhein, an Anthraquinone Compound, and Its Applications in Treating Arthritis: A Review

Abstract: Inflammation is a defensive response of living tissues to damaging agents, which exists in two forms, acute inflammation and chronic inflammation, and chronic inflammation is closely related to arthritis. Currently, the commonly prescribed anti-inflammatory medications are greatly limited by high incidence of gastrointestinal erosions in the clinical applications. Rhein, a bioactive constituent of anthraquinone, exhibits excellent anti-inflammatory activities and therapeutic effects on arthritis with less gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Reportedly, several anthraquinone substances are present in the seeds of S. obtusifolia , of which aurantio-obtusin is the most abundant [ 39 ]. Furthermore, other substances such as rhein, aloe-emodin, and emodin are also known to have arthritis-related anti-inflammatory properties [ 19 , 41 , 42 , 43 ]. These anthraquinones and their derivatives are commonly used as pharmaceutical ingredients [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, several anthraquinone substances are present in the seeds of S. obtusifolia , of which aurantio-obtusin is the most abundant [ 39 ]. Furthermore, other substances such as rhein, aloe-emodin, and emodin are also known to have arthritis-related anti-inflammatory properties [ 19 , 41 , 42 , 43 ]. These anthraquinones and their derivatives are commonly used as pharmaceutical ingredients [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of obtusifolin in OA is currently unknown. As studies have shown that anthraquinones have anti-inflammatory effects [ 16 , 19 , 41 , 42 , 43 ] and the NF-κB pathway is regulated by obtusifolin [ 27 ], we hypothesized that obtusifolin would have a sufficient OA inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…The I κ B kinase P (IKK β )/nuclear transcription factor (NF- κ B) pathway is known as the most promising target for anti-inflammatory drug in recent studies. Rhein is the active metabolite of diacerein, which exerts anti-inflammatory activity mainly through the IKK β /NF- κ B pathway without gastrointestinal damage [ 77 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Several naturally occurring compounds have also been shown to antagonise P2X7R with the potential to be therapeutically valuable. This includes compounds such as Rhein, Emodin, Teniposide, and Baicalein which have all been demonstrated to inhibit P2X7R function in different contexts [112][113][114][115][116]. Whilst these compounds all show P2X7R antagonising properties, there has been limited studies completed in the context of cancer, with only Emodin specifically being investigated in breast cancer cells and shown to limit cancer cell invasion [117].…”
Section: Natural P2x7r Antagonistsmentioning
confidence: 99%